Bacterial leaf blight disease of wheat (Pseudomonas syringae pv. syringae) in Syria: importance, characterization, and spread - Abo Bakr, Abdo; Kassem, Mohammad; Kumari, Safaa; Khatib, Fateh; Husien, Naiem; Nader, Asaad; Moukahel, Abdulrahman (Arab Society of Plant Protection (ASPP), 2023)
The quantity and quality of wheat production are affected by a number of biotic and abiotic stresses, including bacterial wheat leaf blight disease caused by Pseudomonas syringae pv. syringae (Pss). Pss is considered one of the most important seed-borne diseases, as it can play an important role in the spread of the disease by seed and agricultural trade. The seriousness of Pss is that there are no specialized bacterial disinfectants, so it is very important to use rapid and accurate methods to detect Pss in order to limit its transmission through infected seeds to healthy fields. Therefore, the aim of the study was to investigate the spread of bacterial wheat leaf blight diseases in wheat-growing areas in Syria and to produce specific antibodies for Pss detection. In 2022, approximately 500 wheat leaf samples showing symptoms suggestive of bacterial infection were collected from 107 fields in the northern, central and coastal areas of Syria. A total of 56 bacterial isolates were selected using a semi-selective medium, and were characterized further using morphological, biochemical (LOPAT), and pathogenicity tests to identify the isolate’s virulence. Results showed that the bacterial wheat leaf blight disease was observed and recorded in 71.2% of the surveyed fields, and 85.7% of the isolates were found to belong to the genus Pseudomonas. A representative Pseudomonas isolates were further tested by polymerase chain reaction (PCR) using specific primers for the syringomycin production gene. Molecular analyses revealed that 12 isolates belong to Pseudomonas syringae pv. syringae (Pss). The bacterial suspension of one Pss isolate (H6), collected from a wheat field in central Syria, was inactivated by formaldehyde treatment and injected into a rabbit. The quality of produced antiserum was evaluated by Dot-blot Immunoassay using homologous and heterologous antigens, and the results obtained revealed that the produced antiserum was able to detect Pss with no cross-reactivity with other bacterial genera (e.g. Xanthomonas).